RECORD OF ð˜›ð˜©ð˜³ð˜ªð˜±ð˜´ ð˜±ð˜¢ð˜ð˜®ð˜ª KARNY, 1925 (THYSANOPTERA, THRIPIDAE) IN THE STATE OF SÃƒO PAULO, BRAZIL - Monteiro, Renata C.; Zucchi, Roberto A.; Mound, Laurence A. (REVISTA DE AGRICULTURA, 2020)
RECORD OF ð˜›ð˜©ð˜³ð˜ªð˜±ð˜´ ð˜±ð˜¢ð˜ð˜®ð˜ª KARNY, 1925 (THYSANOPTERA, THRIPIDAE) IN THE STATE OF SÃƒO PAULO, BRAZIL